GPI-Anchored Protein Complex, LY6K/TEX101, Is Required for Sperm Migration into the Oviduct and Male Fertility in Mice. Issue 3 (1st March 2014) - Fujihara, Yoshitaka; Okabe, Masaru; Ikawa, Masahito
Abstract: A disintegrin and metallopeptidase domain 3 (ADAM3) is a sperm membrane protein reported to be critical for both sperm migration from the uterus into the oviduct in vivo and sperm binding to the zona pellucida in vitro. In order for ADAM3 to be expressed on the sperm surface, the interaction with testis-expressed gene 101 (TEX101), a glycosylphosphatidylinositol (GPI)-anchored protein, is essential. Without TEX101, ADAM3 is degraded during sperm transition through the epididymis. However, it is also known that TEX101 has to be shed and to disappear from testicular germ cells (TGCs) by the GPI-anchored protein-releasing activity of angiotensin-converting enzyme (ACE) for the correct localization of ADAM3 on the mature sperm surface to take place. Here, we found that in a mouse line with a disruption for another testis-specific GPI-anchored protein, lymphocyte antigen 6 complex, locus K (LY6K), the male mice became infertile and demonstrated a phenotype similar to that found in Adam3 –/–, Tex101 –/–, and Ace –/– mice. LY6K interacted with TEX101 and ADAM3 in the TGCs but disappeared from mature spermatozoa. Differing from more than 10 previously known gene knockout mouse lines that showed male infertility by impaired sperm migration into the oviduct, spermatozoa from Ly6K –/– mice had no aberrance in ADAM3. Thus, LY6K is a newly identified factor involved in sperm fertilizing ability. The lack of effect on ADAM3 in Ly6K –/– mice is indicative of an as yet undefined pathway in the mouse.